UKURAN DEWAN KOMISARIS DALAM MEMODERASI HUBUNGAN ANTARA CORPORATE ENVIRONMENTAL DISCLOSURE DENGAN MANAJEMEN LABA RIIL - Daffa Ardhi Satryo (2022)
This study aims to examine corporate environmental disclosure which consists of environmental policy, environmental pollution, environmental energy, environmental financial, and environmental others aspects on the real earnings management with the board of commissioners size having a role as variables moderating with profitability, leverage, company size and external audit quality as control variables. The data used in this study is secondary data obtained from annual report and sustainability report of non-financial sector companies on the Indonesia Stock Exchange in 2018-2020. A total sample research was 93 firm - year observations and data were tested using STATA 14. The results of the study stated that environmental policy, environmental energy, environmental financial, and environmental others has no significant effect on real earnings management. While environmental pollution has a significant and negative effect on real earnings management. As for the role of moderation, the size board of commissioners size cannot moderate the relationship of environmental policy, environmental pollution, environmental energy, environmental financial, and environmental others with real earnings management. Keywords: Corporate environmental disclosure, board of commissioners size, real earnings management